Can water run uphill on the map? The importance of school cartography for the teaching of geomorphology - Ben, Franciele Delevati (2023)
This research aims to present an activity report on the teaching of Geomorphology that involves models, anaglyph images, and maps of hypsometry and drainage networks. The activities reported in this article are part of a larger project, which elaborates the geoenvironmental atlases of municipalities in the Center-West of Rio Grande do Sul and creates teaching materials to support teachers in these municipal networks. The activity was applied in elementary schools in Jari and Nova Esperança do Sul, RS. Most students already had prior knowledge and could visualize the concepts in anaglyph images and models. However, when interpreting the maps, less than 25% were able to identify high and low points and also the flow direction, which links to the lack of Cartographic Literacy notions: difficulty in creating and reading legends; difficulty inserting symbols on the map; and the memorization of the cardinal points, since 17% of the students indicated that the water can only go to the south - low portion on the map. Thus, it is important to consider teaching Geomorphology focused on the place through diversified strategies based on the notions of literacy and cartographic literacy.